Relevansi Nilai Sosial dalam Antologi Puisi Malu Aku Jadi Orang Indonesia Karya Taufik Ismail dengan Muatan Isi Kurikulum 2013 - Anton Susilo; Yuni Pratiwi; Sunoto Sunoto (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2018)
This study aims to describe social values based on religious, family, education and relevance to content content contained in the curriculum 2013. This research uses descriptive qualitative methods. The findings of social value research based on religious, family and educational attributes concerning the spiritual social values associated with a human belief in God YME, vital social values, concerning the function of affection or affection, and the latent function of educational institutions related to maintaining social integration. Then the relevance to the content content in the curriculum 2013, related to KI, KD, and Indicators contained in the learning of SMP class VIII.